2010
DOI: 10.2495/etox100061
|View full text |Cite
|
Sign up to set email alerts
|

Factors controlling the release of arsenic from mining tailings

Abstract: Some mine tailings pools in the Mine District of Guanajuato, Mexico, present a varied distribution and temporal and spatial concentration of elements that are potentially toxic, such as manganese, cadmium and zinc. These elements were detected in majority concentrations, and arsenic was present in the two major oxidation states As(III) and As(V). The highest arsenic concentration in the surrounding surface water reservoirs was detected when a rainy seasons occurred, which in turn is mainly a function of pH and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The introduction of OH − could increase the replacement of arsenic from sediment. Increase of pH could also enhance the negative charge of the sediment particle surface, which could enhance the repulsion between arsenic species in the solution and the sediment surface (Rodríguez-Cruz et al, 2005;Rubinos et al, 2010;Rubio-Campos et al, 2010;Shen, 2000;Sugihara et al, 2008). However, previous research has reported that the increase of pH had a negative effect on the adsorption of anionic surfactants due to the reversion of the surface charge (Camacho et al, 1996;Huang and Van Benschoten, 2000;Li et al, 2012;Mushtaq et al, 2015).…”
Section: Influence Of Phmentioning
confidence: 99%
“…The introduction of OH − could increase the replacement of arsenic from sediment. Increase of pH could also enhance the negative charge of the sediment particle surface, which could enhance the repulsion between arsenic species in the solution and the sediment surface (Rodríguez-Cruz et al, 2005;Rubinos et al, 2010;Rubio-Campos et al, 2010;Shen, 2000;Sugihara et al, 2008). However, previous research has reported that the increase of pH had a negative effect on the adsorption of anionic surfactants due to the reversion of the surface charge (Camacho et al, 1996;Huang and Van Benschoten, 2000;Li et al, 2012;Mushtaq et al, 2015).…”
Section: Influence Of Phmentioning
confidence: 99%